2022
DOI: 10.3390/ph15010082
|View full text |Cite
|
Sign up to set email alerts
|

In Silico Design, Synthesis, and Biological Evaluation of Anticancer Arylsulfonamide Endowed with Anti-Telomerase Activity

Abstract: Telomerase, a reverse transcriptase enzyme involved in DNA synthesis, has a tangible role in tumor progression. Several studies have evidenced telomerase as a promising target for developing cancer therapeutics. The main reason is due to the overexpression of telomerase in cancer cells (85–90%) compared with normal cells where it is almost unexpressed. In this paper, we used a structure-based approach to design potential inhibitors of the telomerase active site. The MYSHAPE (Molecular dYnamics SHared Pharmacop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 85 publications
0
9
0
Order By: Relevance
“…The MM-GBSA approach employs molecular mechanics, the generalized Born model, and the solvent accessibility method to elicit free energies from structural information circumventing the computational complexity of free-energy simulations wherein the net free energy is treated as a sum of a comprehensive set of individual energy components, each with a physical basis [ 55 ]. The conformational entropy change—TΔS—can be computed by normal-mode analysis on docking poses, but many authors have reported that the lack of the evaluation of the entropy is not critical for calculating the MM-GBSA (or MM-PBSA) free energies for similar systems [ 56 , 57 , 58 , 59 , 60 ]. For these reasons, the entropy term–TΔS was not calculated to reduce computational time.…”
Section: Methodsmentioning
confidence: 99%
“…The MM-GBSA approach employs molecular mechanics, the generalized Born model, and the solvent accessibility method to elicit free energies from structural information circumventing the computational complexity of free-energy simulations wherein the net free energy is treated as a sum of a comprehensive set of individual energy components, each with a physical basis [ 55 ]. The conformational entropy change—TΔS—can be computed by normal-mode analysis on docking poses, but many authors have reported that the lack of the evaluation of the entropy is not critical for calculating the MM-GBSA (or MM-PBSA) free energies for similar systems [ 56 , 57 , 58 , 59 , 60 ]. For these reasons, the entropy term–TΔS was not calculated to reduce computational time.…”
Section: Methodsmentioning
confidence: 99%
“…We discovered stable compounds and used the final ten nanoseconds of data for analysis, and snapshots were taken at every 100 picoseconds. The entropy term −TΔS was not calculated to reduce computational time, as previously reported [ 43 , 44 , 45 ].…”
Section: Methodsmentioning
confidence: 99%
“…Three MD simulation replicas of 100 ns each were carried out using a Desmond 6.5 [24] using the OPLS4 force field for each complex FTSJ1/DAP, FTSJ1/SAM, and FTSJ1/NV848, NV914, and NV930. The system setup and the simulation options are the same as reported in previous manuscripts [25][26][27][28]. Initial velocities were determined with random seeds.…”
Section: Molecular Dynamics and Mm-gbsa Calculationsmentioning
confidence: 99%